2022
DOI: 10.3390/foods11040501
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Cooking Enriches the Nanoscale and Short/Long-Range Orders of the Resulting indica Rice Starch Undergoing Storage

Abstract: The chain reorganization of cooked starch during storage plays an important role in the performance of starchy products such as rice foods. Here, different analytical techniques (such as small-angle X-ray scattering) were used to reveal how microwave cooking influences the chain assembly of cooked indica rice starch undergoing storage for 0, 24, or 48 h. While stored, more short-range double helices, long-range crystallites, and nanoscale orders emerged for the microwave-cooked starch than for its conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The results indicated the structure of native starch granules was adequately destroyed by the hydrothermal effects during cooking. [ 10 ] When studying the changes of morphological structures of boiled jasmine rice under different temperature conditions, it was found that the SEM of the internal endosperm of rice showed the same porous and sponge‐like texture with the increase of cooking temperature. [ 18 ] For electric rice‐cooker cooking treatment, the voids inside the cooked germ rice E2 appeared as a net‐like structure, but this structure was not found for the E1, indicating that more starch leached out during longer cooking time in the electric rice‐cooker.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated the structure of native starch granules was adequately destroyed by the hydrothermal effects during cooking. [ 10 ] When studying the changes of morphological structures of boiled jasmine rice under different temperature conditions, it was found that the SEM of the internal endosperm of rice showed the same porous and sponge‐like texture with the increase of cooking temperature. [ 18 ] For electric rice‐cooker cooking treatment, the voids inside the cooked germ rice E2 appeared as a net‐like structure, but this structure was not found for the E1, indicating that more starch leached out during longer cooking time in the electric rice‐cooker.…”
Section: Resultsmentioning
confidence: 99%
“…The study found microwave-cooked starch showed more nanoscale orders, long-range crystallites, and short-range double helices during storage than the conventionally cooking. [10] Therefore, the influences of cooking methods (electric ricecooker and microwave) on the microstructure, rheological behavior, textural properties, aromatic characteristics, and in vitro starch digestion of the cooked germ rice were systematically evaluated in this study. In addition, the relationship between microstructures and digestion of rice starch under different cooking conditions was also discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeng et al [42] found that the addition of yeast β-glucan and proteins significantly inhibited the gelatinization and retrogradation of starch in whole-wheat bread, resulting in a lower glycemic index. Similarly, Xiong et al [43] reported that microwave-cooked starches showed more shortrange double helices, long-range microcrystals, and nanoscale units than conventionally cooked starches. Notably, little is known about the role of hydrocolloids in the human gastrointestinal tract, leading to uncertainty about the exact mechanism of their prevention of diabetes.…”
Section: Glycemic-lowering Propertiesmentioning
confidence: 94%